Computational studies, design and synthesis of Pd(II)-based complexes: Allosteric inhibitors of the Human Topoisomerase-IIα - Rocha, Fillipe V.; Farias, Renan L. [UNESP]; Lima, Mauro A.; Batista, Victor S. [UNESP]; Nascimento-Júnior, Nailton M. [UNESP]; Garrido, Saulo S. [UNESP]; Leopoldino, Andréia M.; Goto, Renata N.; Oliveira, Adriano B.; Beck, Johannes; Landvogt, Christian; Mauro, Antônio E. [UNESP]; et al. (Elsevier, 2019)
Herein, a robust docking protocol was developed by using a low-cost workflow to highlight the modulation at ATPase domain from Human Topoisomerase-IIα (TOP2A) towards four novel Pd(II)-complexes bearing N,S-donor ligands. In vitro TOP2A inhibition assay confirmed the ability of them to prevent the enzyme functions into concentration ranging at 6.25–25 μM. These results exhibited more effectivity than anticancer agent etoposide (35 μM) and merbarone (40–50 μM). The compounds were screened via Resazurin assay against MCF-7, MDA-MB-231 (Human breast), DU-145 (Human prostate), A549 (Human lung) and Cal27 (Human tongue) tumor cell lines revealing great cytotoxic effects, primarily to MCF-7 (IC50 = 1.81–4.46 μM). As well, 1–4 exhibited their selectivity index (SI) higher than cisplatin against HEK-293 (human kidney) normal cells, at least 11.6-fold (SI1–4 = 1.4–5.0; SIcis = 0.12). Further, Red Blood Cell hemolytic test suggested in vitro non-toxic character for compound 4, previously evaluated as the most effective TOP2A inhibitor.